Wage Gains from Foreign Ownership: Evidence from Linked Employer-Employee Data - János Köllő; István Boza; László Balázsi (Institute of Labor Economics (IZA), 2020)
We compare wages in multinational enterprises (MNEs) versus domestic firms, the earnings of domestic firm workers with past, future and no MNE experience, and estimate how the presence of ex-MNE peers affects the earnings of domestic firm employees. The analysis relies on monthly panel data covering half of the Hungarian population and their employers in 2003-2011. We identify the returns to MNE experience from changes of ownership, wages paid by new firms of different ownership, and the movement of workers between enterprises. We find high contemporaneous and lagged returns to MNE experience and significant spillover effects. Foreign acquisition has a moderate wage impact but there is a wide gap between new MNEs and domestic firms. The findings suggest that MNE experience is valued in the high-wage segment of the local economy, connected with the MNEs via worker turnover.
Keywords: F23; J31; J62; 330; wage differentials; foreign direct investment; Hungary; multinational enterprises; wage spillover